ANALISIS KELAYAKAN FINANSIAL SISTEM PERTANIAN GAMBIR DI NAGARI SIALANG, KAPUR IX, KECAMATAN LIMA PULUH KOTA - Yusrizal Husein; Suardi Tarumun; Shorea Khaswarina (Fakultas Pertanian, Universitas Riau, 2018)
This research was aimed to analyze the financial feasibility and sensitivity of gambir farming tothe changes in input and output prices in Nagari Sialang Kapur IX Sub District of Lima PuluhKota District. The research sites was selected intentionally. The data used include primary andsecondary data. Primary data were obtained from questionnaires and interviews directly tofarmers. Secondary data was obtained from various literatures, printed media and some agenciessuch as BPS and Agricultural Agency. Data was collected in April 2017 and analyzed using NetPresent Value (NPV), Net Benefit Cost Ratio (Net B/C) and Internal Rate of Return (IRR)criteria. The results showed that gambir farming in Nagari Sialang Kapur IX of Lima Puluh KotaDistrict is economically feasible; it has a positive NPV value of IDR 521,166,238. Net BenefitCost Ratio is greater than one that is 5.59 and IRR value is bigger than Social Opportunity Cost ofCapital (SOCC). Gambir farming in Nagari Sialang Kapur IX is still feasible to be cultivated ifthe cost of production increase up to 20% or if the selling prices decrease up to 20%.